OS ECOSSISTEMAS COSTEIROS NO ENSINO MÉDIO: ANÁLISE DAS PRÁTICAS DOCENTES E DOS CONHECIMENTOS DOS ALUNOS SOBRE O TEMA - Mendonca, Petrina Cantamissa Mallosto (2020)
This research brought as its object the teaching of the content of Ecology with a focus on the theme of coastal ecosystems by high school teachers from public schools in the state of Guarapari - ES, for which it proposes a methodological practice of an in